2003
DOI: 10.1128/jb.185.9.2944-2951.2003
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificity and Expression of Three 2,3-Dihydroxybiphenyl 1,2-Dioxygenases from Rhodococcus globerulus Strain P6

Abstract: Rhodococcus globerulus strain P6 contains at least three genes, bphC1, bphC2, and bphC3, coding for 2,3-dihydroxybiphenyl 1,2-dioxygenases; the latter two specify enzymes of the family of one-domain extradiol dioxygenases. In order to assess the importance of these different isoenzymes for the broad catabolic activity of this organism towards the degradation of polychlorinated biphenyls (PCBs), the capacities of recombinant enzymes expressed in Escherichia coli to transform different chlorosubstituted dihydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
37
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 41 publications
2
37
1
Order By: Relevance
“…Overall, the present data agree reasonably well with steadystate kinetic parameters and relative activities reported by McKay et al (24). Both studies evaluated the steady-state kinetic parameters of DHBD P6 -I and -III for DHB and 2Ј-and 3Ј-Cl DHB.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Overall, the present data agree reasonably well with steadystate kinetic parameters and relative activities reported by McKay et al (24). Both studies evaluated the steady-state kinetic parameters of DHBD P6 -I and -III for DHB and 2Ј-and 3Ј-Cl DHB.…”
Section: Discussionsupporting
confidence: 81%
“…Based on the higher specificity of these enzymes for some Cl DHBs than for unchlorinated DHB, it has been suggested that they may have been recruited by R. globerulus P6 to improve its PCB degradation (24,37). However, the present results demonstrate that relatively high specificity constants for Cl DHBs are not unique to the single-domain DHBDs.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Cell extracts were prepared as previously described (39). Protein concentrations were determined by the Bradford method (6).…”
mentioning
confidence: 99%